Replication of a Maori Ethnographic Textile Hem Border Pattern - Lisa McKendry (EXARC Journal)
Replication of archaeological and ethnographic Māori textiles, under the direction of customary knowledge and previous practical experience, can provide a more nuanced understanding of the manufacture of taonga (treasures) made from fibre materials. A case study is presented here from the unique perspective of a weaver who is also an archaeologist, and familiar with the essential components of replication work. This paper introduces tāniko, a Māori weft-twining technique, and the replication of a unique tāniko pattern on the hem border of an ethnographic kākahu (cloak), known as ‘the Stockholm cloak’. The project follows experimental archaeology standards and customary Māori practices and protocols for all processes and steps involved. A variation of the known tāniko technique was identified, alongside an appreciation of the enormous skill involved not only in the weaving technique but in the fibre preparation and processing. Further, a renewed awareness was acquired for the importance of skilled mentors willing to share their fibre working expertise. This type of study provides empirical data to the archaeological discipline, while supporting, and contributing to, the continuity of customary knowledge systems.